Outros grandes sertões: cruzamentos entre sertão literário, nação brasileira e fotografia documental - Agostineti, Kaique (2013)
This work seeks to understand the process of the Brazilian nation in photographic narrative about the Sertão. Thus, we analyze the ideas of authors who wrote about modern nation and those who created narratives that proposes the existence of a nation from the Sertao category. First, we analyze works of national literature as Os Sertões de Euclides da Cunha and Grande Sertão: Veredas by João Guimarães Rosa. Subsequently, we discuss the passage of literary Sertão for photography. We understand the photographic language and medium, for its unique characteristics, generate images that differ from the hinterland described in the pages of national literature. Then we analyze this backcountry in the case of Flávio de Barros’s photographs in Canudos and photographic work Sertões: Luz & Trevas by Maureen Bisilliat. Thus, we launched the proposal for analyzing the intersections between the literary sertão, the modern nation and the documentary photography.